Temperature-dependent charge transport in polymer-sorted semiconducting carbon nanotube networks with different diameter distributions - Brohmann, Maximilian; Rother, Marcel; Schießl, Stefan Patrick; Zaumseil, Jana (The journal of physical chemistry. C, Energy, materials, and catalysis, 2018)
The availability of purely semiconducting single-walled carbon nanotube (s-SWCNT) dispersions has prompted their widespread application in solution-processed thin-film transistors with excellent device performance but has also raised the question of how their precise composition influences charge transport properties in random networks. Here, we compare hole and electron transport in three different polymer-sorted s-SWCNT networks from nearly monochiral (6,5) nanotubes (diameter 0.76 nm) to mixed networks of s-SWCNTs with medium (0.8–1.3 nm) and large (1.2–1.6 nm) diameters. Temperature-dependent field-effect mobilities are extracted from gated four-point probe measurements that exclude any contributions by contact resistance and indicate thermally activated transport. The mobility data can be fitted to the fluctuation-induced tunneling model, although with significant differences between the network compositions. The network with the broadest diameter and thus bandgap range results in the strongest temperature dependence in agreement with numerical simulations based on a random resistor model of nanotube junctions. However, the experimental data for mixed networks of large diameter nanotubes and their deviation from the simple junction model implies a significant contribution of intra-nanotube transport with its specific diameter and temperature dependence to the overall charge transport properties of the network.